If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -6 = 2(5x + -4) Reorder the terms: -6 + 10x = 2(5x + -4) Reorder the terms: -6 + 10x = 2(-4 + 5x) -6 + 10x = (-4 * 2 + 5x * 2) -6 + 10x = (-8 + 10x) Add '-10x' to each side of the equation. -6 + 10x + -10x = -8 + 10x + -10x Combine like terms: 10x + -10x = 0 -6 + 0 = -8 + 10x + -10x -6 = -8 + 10x + -10x Combine like terms: 10x + -10x = 0 -6 = -8 + 0 -6 = -8 Solving -6 = -8 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2y+2-y=9 | | 3x-(x+5-1)+(x-x+4)= | | f^2+3f-70= | | X^2-6x+10=o | | (w*1)+(1-w)*11=3 | | 5-y-3y=27 | | f(x)=x^2-5x-150 | | x^2=56+x | | 11x+20=15x | | 6x^2+41x-7= | | m^2+4m-60= | | 2(x+6)=x-3 | | 2y-3(4-2y)=2(y-3)+6 | | 21/44 | | 5x-9=x+19 | | 5x^3+33x^2+44x+2=-18 | | 27-2x=x^2+4x | | 7x-2/3=14 | | x^3+.6x^2-7.7x+1.4=0 | | 7m+1=m^2+13 | | y=f(x-4) | | 3(4k-1)+2(5k-3k)=7k | | 2(9y^2+12+4)=0 | | 2t-4t=4 | | -2x+21=x+9 | | 3x^4y^6+6x^5y^5= | | (49x^4)^1/2 | | 9x-2.1+.9=.2(5-x) | | 9x+20y=-50 | | 4.4(n-5)+(-3n)=20 | | x+11=2*x+5 | | x+3x+1=7 |